Planes, Trains, and Armored Mobiles: Introducing a Dataset of the Global Distribution of Military Capabilities. - Gannon, J Andrés (International Studies Quarterly, 2023)
This article introduces a dataset on disaggregated national military capabilities from 1970 to 2014, drawn from the International Institute for Strategic Studies Military Balance. While practitioners have long recognized the importance of what weapons states own, scholars have largely examined surrounding questions in piecemeal fashion due to data limitations. The Distribution of Military Capabilities dataset identifies the weapons portfolios of states over the past half century at various levels of aggregation suitable to a wide variety of research questions. This paper begins by explaining the value of data on disaggregated national military capabilities, the data's scope, and the data collection process, including the creation of a new modular typology of weapons categories consistent across time and space. I then identify some initial trends about changes in the distribution of military capabilities and their implications for China's military rise. These data allow scholars to better investigate important questions concerning power projection, military innovation, conflict outcomes, the use of force decisions, and interest group lobbying.